Emotion Regulation Strategies as Mediators of the Relationship Between Internalizing Psychopathology and Sleep-Wake Problems During the Transition to Early Adolescence: A Longitudinal Study. (May 2021) - Tomaso, Cara C.; Johnson, Anna B.; James, Tiffany D.; Nelson, Jennifer Mize; Mason, W. Alex; Espy, Kimberly Andrews; Nelson, Timothy D.
Internalizing psychopathology, including depression and anxiety, has been associated with sleep-wake problems among youth. Although transdiagnostic theories of psychopathology posit that emotion dysregulation explains many of the symptoms associated with internalizing psychopathology, examination of regulatory mechanisms underlying this association is limited, particularly during the transition to early adolescence when risk for affective dysregulation and sleep-wake problems is heightened. Using a longitudinal design with a youth community sample ( N = 278), the current study found a positive, indirect effect of internalizing psychopathology (X ¯ age = 9.84) on later sleep-wake problems (X ¯ age = 14.53) via higher levels of a more maladaptive emotion regulation strategy (i.e., expressive suppression), with no evidence of an indirect effect of a more adaptive strategy (i.e., cognitive reappraisal;X ¯ age = 12.02). Findings have important clinical implications for targeting the reduction of maladaptive emotion regulation strategies, such as expressive suppression, in order to address sleep problems among youth with internalizing psychopathology.